Analyze of Audit Delay With The Roles Reputation, Fee, Traits, and Tenure as Mediation - Amelia, Siti Nur; Abbas, Dirvi Surya (Universitas Muhammadiyah Malang, 2026)
Purpose: This study examines the effect of audit firm reputation, audit fee, and auditor characteristics including certification and gender on audit delay, with audit tenure as a mediating variable, focusing on industrial companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Methodology/approach: A quantitative research design was employed using panel data regression analysis to investigate both direct and indirect relationships among the variables. The study utilized 425 firm-year observations from 85 manufacturing companies, analyzing the mediating effect of audit tenure through the Sobel test and path analysis. Findings: The results reveal that audit firm reputation has a positive and significant effect on audit delay, indicating that reputable or Big Four–affiliated firms are associated with longer audit completion periods. In contrast, audit fee has a negative and significant effect, suggesting that higher audit fees accelerate audit completion. Auditor certification, auditor gender, and audit tenure do not have a significant direct effect on audit delay. Furthermore, audit fee significantly influences audit tenure, while audit tenure does not mediate the relationship between audit firm reputation, audit fee, and auditor certification on audit delay. However, audit tenure significantly mediates the relationship between auditor gender and audit delay. Practical implications: These findings suggest that both institutional factors (audit firm reputation) and economic factors (audit fee) play important roles in determining audit timeliness. While reputable firms may prioritize procedural thoroughness, adequate audit compensation enhances efficiency. The selective mediating role of audit tenure also indicates that engagement continuity does not universally improve audit timeliness. Originality/value: This study contributes to the audit delay literature in emerging markets by integrating firm-level and auditor-level determinants and examining audit tenure as a mediating factor, offering theoretical and managerial implications for improving audit quality and timeliness in Indonesia’s manufacturing sector.